Influencia de los haplotipos del CCR5-CCR2 en la transmisión sexual de la infección por HIV-1 en parejas discordantes que viven en la República Argentina - Paradiso, Patricia (2016)
Acquired Immunodeficiency Syndrome (AIDS) was described over thirty years ago and human immunodeficiency virus (HIV) considered as its causative agent. Infection involves interaction between viral cover glycoproteins gp120/41 and molecules that belong to the Cluster of Differentiation group 4 (CD4) expressed over target cells´ surface: T lymphocytes, macrophages and dendritic cells. This event is closely followed by the binding to a cellular chemokine receptor (CCR): CCR5 and/or CXCR4, to allow according tropism, fixation and viral incoming to the cell.\nFor establishing the relationship between the presence of co-receptor genes´ mutations with susceptibility or protection against infection, we recruited heterosexual couples whose members should be infected and non- infected, maintaining unprotected sexual intercourse within argentine population. They are known as discordant, serodiscordant or with mixed serological condition. Both members of these couples were serologically screened for detecting antigens and antibodies against HIV, HVB (Hepatitis B Virus), HCV (Hepatitis C Virus) and HTLV (Human T Lymphotropic Virus) at the beginning and ending of this protocol.\nOur main aim was to settle down the consequence of differences in CCR5-CCR2 haplotypes co-receptors´ over HIV infection in discordant Argentinean heterosexual couples and as secondary aims to detect other viral infections (HBV, HCV y HTLV) in the whole group; to compare allelic, haplotypic and haplotypic combinations frequencies of these co-receptors between infected and uninfected members of the couples and with Argentinean population control group and to compare these results with those obtained for the same genetic markers in perinatal transmission.\nWe developed an observational, descriptive, cohort, double blind study. Seronegative exposed (SNE) and seropositive (SP) individuals from heterosexual Argentinean couples were recruited. Haplotype characterization was done through PCR (Polymerase Chain Reaction) and RFLP-PCR (Restriction Fragment Length Polymorphism).\nBoth members of 63 heterosexual discordant couples were included. Some partners decided not to concur to the interviews but seven SP women, one SP man and one SNE woman confirmed their discordant partner?s condition and were included. All of them are adults, living in the República Argentina, signed informed consent and received wide information about this investigation aims. The protocol´s development period was: minimum lapse one year, maximum lapse five years (?=2.53 years ± SD=1.22). SPs are 40 women and 31 men and SNEs are 31 women and 33 men, no statistical differences between both cohorts were described according sex. 99 blood donors from argentine population from the ?Banco de Sangre del Hospital J. P. Garrahan? were established as control group (CG).\nCo-infection analysis revealed that SP´s frequencies were significantly higher (23.9%) when compared with SNE (3.1%) (p=0.0005, RR=7.66 IC 95% = 1.84-31.88). Comparing SNE with Argentinean population frequencies or SP with HIV reactive patients no significant differences were detected.\nHHG2 (?32) was the only one haplotype that showed statistical importance comparing SNE and CG (OR = 5.92 IC 95%: 1.59-21.99, p=0.0045). SP vs. CG and SP vs. SNE were not significantly different.\nHHE/HHE genotype was associated with greater infection risks and HHE/HHF2 showed protector effect (HHE/HHE: OR=5.09 IC (95%) 1.05-24.63, p=0.0428; HHE/HHF2: OR=0.13 IC (95%) 0.03-0.50, p=0.0039. These results agree with those reported for perinatal transmission in our population.\nIn this study we could demonstrate through genotyping CCR5-CCR2 haplotypes of HIV co receptors and their possible combinations in serodiscordant couples belonging to Argentinean population, that there is significant association with a predisposing factor: HHE/HHE and a protector one: HHE/HHF2. This analysis´ value resides over the fact that there are no publications on this subject made in our population until these days and that recruitment of these couples of difficult access, allowed us to recognize factors that may condition susceptibility to infection.\nInfection is the consequence of intercurrent factors involving host and virus; we cannot fail to mention that genetic variability of these co receptors is only one single event within conditioning possibilities of viral transmission.